Case Report: Stage IIIc primary malignant mixed Müllerian tumor of the fallopian tube: A case of 5-year disease-free survival after cytoreductive surgery combined with peritoneal resection and adjuvant chemotherapy with paclitaxel plus carboplatin - Xiao, Xiaoli; Ma, Ruiqing; Shi, Lianyao; Wang, Cong; Chen, Jie; Lu, Yiyan; Wang, Yufeng; Zhai, Xichao; Fu, Fengxian (Frontiers in Oncology, 2022)
Malignant mixed Müllerian tumor (MMMT) of the fallopian tube is rare, has a poor prognosis, and is traditionally treated with as much tumor tissue resection as possible. For the patient with fallopian tube MMMT, complete resection of the macroscopic malignancy (removal of the tumor invading the viscera and the peritoneum infiltrated by the tumor) is a prerequisite for long-term survival. We report a case of stage IIIc MMMT of the fallopian tube treated by cytoreductive surgery (CRS), peritoneal resection, adjuvant chemotherapy (paclitaxel plus carboplatin) five years earlier, with a 5-year post-treatment tumor-free survival. Optimal CRS helps to achieve a cytoreduction score of 0 (CC-0), which may be attributed to the technical specifications for peritoneal resection in the pelvic peritoneum. Postoperative chemotherapy combining platinum and paclitaxel is the most potent adjuvant therapy.